(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This review highlights the importance of measuring fuel consumption, draft force, and ground speed of agricultural tractors during tillage operations. Accurate estimations help in selecting conservation practices, optimizing machinery usage, and improving energy efficiency. Various measurement methods are analyzed, discussing their advantages and limitations.